Comparison of haemodynamic alteration with laryngeal mask airway and endotracheal tube in intermediate duration of gynaecological operation (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Laryngeal mask airway insertion causes less changes of haemodynamic parameters. As haemodynamic changes during laryngoscopy and endotracheal intubation as result of intense stimulation of sympathetic nerves system. Objective To find out the effective airway management by LMA during controlled ventilation, to avoid laryngoscopic and intubation induced haemodynamic changes and to avoid laryngospasm and bronchospasm. Method A total number of 100 patients ASA grade I & II were selected randomly as per inclusion and exclusion criteria in two groups. Fifty in each group. In group A used LMA and in group B used ETT during general anaesthesia in intermediate duration of gynaecological operation. Pulse,NIBP,SpO2 were recorded in perioperatively. Result Pulse, blood pressure were significant between the two groups (p